The Use of Endogenous Variables in Dynamic Models of Investment - Gould, John P. (Quarterly Journal of Economics, 1969)
I. Introduction, 580. — II. The determination of desired capital stock, 581. — III. Jorgenson's 1963 investment model, 585. — IV. The adjustment mechanism, 588. — V. The predictive powers of the model, 592. — VI. Estimation and prediction, 597. — VII. Conclusions, 599.